2016
DOI: 10.18632/oncotarget.11505
|View full text |Cite
|
Sign up to set email alerts
|

ATF6α regulates morphological changes associated with senescence in human fibroblasts

Abstract: Cellular senescence is known as an anti-tumor barrier and is characterized by a number of determinants including cell cycle arrest, senescence associated β-galactosidase activity and secretion of pro-inflammatory mediators. Senescent cells are also subjected to enlargement, cytoskeleton-mediated shape changes and organelle alterations. However, the underlying molecular mechanisms responsible for these last changes remain still uncharacterized. Herein, we have identified the Unfolded Protein Response (UPR) as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 43 publications
(47 reference statements)
1
57
0
1
Order By: Relevance
“…Moreover, as shown in the hepatocellular carcinoma model, ATF6 may be involved in the regulation of cell proliferation (57) or in the sensitivity to chemotherapy in leukemia cells (58). Data also suggest ATF6 contribution to cancer progression by shaping tumor microenvironment (59) as well as in the induction of the senescent phenotype (60). In summary, accumulating evidence suggests that activation of the UPR may affect multiple aspects related to cancer progression beyond its classical role in tumor adaptation against hypoxia.…”
Section: Atf6mentioning
confidence: 92%
“…Moreover, as shown in the hepatocellular carcinoma model, ATF6 may be involved in the regulation of cell proliferation (57) or in the sensitivity to chemotherapy in leukemia cells (58). Data also suggest ATF6 contribution to cancer progression by shaping tumor microenvironment (59) as well as in the induction of the senescent phenotype (60). In summary, accumulating evidence suggests that activation of the UPR may affect multiple aspects related to cancer progression beyond its classical role in tumor adaptation against hypoxia.…”
Section: Atf6mentioning
confidence: 92%
“…However, several experiments in vitro have revealed that the ER stress-induced UPR is rather the inducer of cellular senescence and not only an outcome. Druelle et al [13] reported that ATF6α signaling controls many morphological aspects of the replicative senescence of human fibroblasts. The silencing of ATF6α signaling could partly reverse the ER expansion and SASP of senescent cells.…”
Section: Er Stress In the Aging Processmentioning
confidence: 99%
“…ER stress is closely associated with both aging and AD pathology (see below). For instance, ER stress is connected to the generation of cellular senescence [12][13][14]. The number of senescent cells progressively increases with aging.…”
Section: Introductionmentioning
confidence: 99%
“…Also, ATF6a-dependent transcription increased after NBR1 abrogation, as demonstrated by a reporter assay. Recently, it has been reported that ATF6a regulates the morphologic changes associated with cellular senescence (39).…”
Section: Discussionmentioning
confidence: 99%